Comparative financial performance analysis of commercial banks in India - R, Chethan; F, Sayyad Jafar C. (BOHR International Journal of Finance and Market Research, 2024)
Commercial banks are financial institutions that perform the functions of accepting deposits from the general public and giving loans for investment with the aim of earning profit. These banks play a key role in the growth and development of an economy. In India, commercial banks are broadly classified into public sector commercial banks, private sector commercial banks, and foreign commercial banks. In the present study, the researchers have made an attempt to examine the financial performance analysis of public sector and private sector commercial banks in India. The study covers the top five public sector commercial banks and the top five private sector commercial banks. The study is based on secondary data extracted from books, journals, financial statements of the banks under study, and other websites. The study period is 5 years—from March 2019 to March 2023. Financial performance and Market capitalization parameters along with key banking ratios were used for the analysis and ajudgmental sampling technique was used for selecting the sample.